Prevalence of genital warts in Campo Grande – Mato Grosso do Sul in the period 2006 to 2009 - Simão, Tassiana E (2010)
This study aims to estimate the prevalence of condyloma lesions caused by infection with human papillomavirus (HPV), in Campo Grande – Mato Grosso do Sul in the period 2006 to 2009. It was a cross-sectional study of prevalence conducted through a survey of data provided by the National Notifiable Diseases (SINAN) of Campo Grande in the period 2006 to 2009, after request filed. Were reported 961 cases of condyloma lesions, with prevalence among males; in 2008 was higher numbers of notifications. In 2009 occurred the greatest number of cases in patients younger than 10 years. The vast majority were diagnosed under 3 months. Was observed growing areas of infection throughout the period studied, with emphasis on new cases in children younger than 10 years, which implies increased incidence in pregnant patients resulting in higher rate of vertical transmission, and is also notorious jump observed in the number of cases in the transition from pre-adolescence and adolescence, inferring the onset of early sexual activity of these patients.